2008
DOI: 10.4161/cbt.7.10.6660
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of RCK/p54 expression by RNAi inhibits proliferation of human colorectal cancer cells in vitro and in vivo

Abstract: Colorectal cancer is the third most common cancer in both men and women around the world. Although much progress of the mechanism of colorectal carcinogenesis has been made, the studies centering on the mechanisms of tumorigenesis are much needed to be further exploited. The overexpression of RCK/p54 gene, a member of the DEAD box protein/RNA helicase family, has been found in this malignancy. Roles of RCK in the development of colon cancer, however, are unknown. In this report, we explored whether RCK/p54 pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Given the role of DDX6 in PTCH1 mRNA translation, DDX6 overexpression would result in PTCH1 overexpression, a feature typical of pancreatic cancer. Interestingly, DDX6 is overexpressed in several cancers (Nakagawa et al 1999;Hashimoto et al 2001;Miyaji et al 2003;Lin et al 2008;Sen et al 2015;Taniguchi et al 2015), opening the possibility that translational regulation by DDX6 plays an important role in malignant transformations.…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of DDX6 in PTCH1 mRNA translation, DDX6 overexpression would result in PTCH1 overexpression, a feature typical of pancreatic cancer. Interestingly, DDX6 is overexpressed in several cancers (Nakagawa et al 1999;Hashimoto et al 2001;Miyaji et al 2003;Lin et al 2008;Sen et al 2015;Taniguchi et al 2015), opening the possibility that translational regulation by DDX6 plays an important role in malignant transformations.…”
Section: Discussionmentioning
confidence: 99%
“…Can both promote and repress translation initiation: associates with P-bodies, ATP hydrolysis allows release from P-bodies and translation initation [32][33][34][35][36][37] 58,65 Developmental roles in many species [57][58][59][60][61][62] Overexpression in several cancers [53][54][55][56] Stimulation of cell cycle progression and proliferation [70][71][72][73][74] Cell cycle progression/proliferation Dhh1p important for recovery from DNA damageinduced G1/S cell cycle arrest in yeast DDX6 required for S-phase progression and cell viability in HeLa and LoVo cells, 73,74 and proliferation in xenograft models 74 (siRNA studies)…”
Section: Translationmentioning
confidence: 99%
“…Several studies, with both the human DDX6 and the yeast Dhh1p, have indicated that this protein acts as a positive regulator of cell cycle progression: Dhh1p has been shown to be important for recovery from DNA-damage-dependent G1/S cell cycle arrest, 72 while two separate studies demonstrated that siRNA knockdown of DDX6 resulted in S-phase cell cycle arrest. 73,74 Furthermore, these studies showed that siRNA knockdown of DDX6 resulted in a reduction in cell viability, 73 as well as an increase in cell apoptosis and a reduction in their ability to form tumors in xenograft models. 74 Additionally, overexpression of DDX6 was shown to increase expression of the oncogene c-Myc, consistent with the idea that it would have a positive effect on cell proliferation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We show that Ddx42p overrode this effect under various conditions, and Ddx42p knockdown had a proapoptotic effect (Figures 4 and 5). Interestingly, other Ddx proteins, such as Ddx25 (Gutti et al, 2008) and rck/ p54 (Lin et al, 2008b), also promote cell proliferation, and their knockdown induces apoptosis, by yet unknown mechanisms. Ddx42p(1-737), lacking the C-terminal domain that binds to ASPP2, did not interfere with cellular survival, and was incapable of counteracting ASPP2-induced apoptosis.…”
Section: Ddx42p Counteracts Aspp2mentioning
confidence: 99%